Pengaruh Harga Kamar dan Fasilitas terhadap Keputusan Menginap pada Hotel Simpang Baru Lahat - Mujari Mujari (IPM2KPE, 2020)
This study aims to determine the effect of room prices on the decision to stay at the Hotel Simpang Baru Lahat, the influence of facilities on the decision to stay at the Hotel Simpang Baru Lahat, and the influence of room prices and facilities on the decision to stay at the Hotel Simpang Baru Lahat. The results showed the price of rooms and facilities showed a calculated F value> F table (96.548> 5.59) and a significance value (0.000 <0.05). As well as the price of the room, with the value of t count> t table (10.626> 1.996). For facility variables with t count> t table (10.626> 1.996). Conclusions, room rates, the effect of facilities, and the price of rooms and facilities have a positive and significant effect on the decision to stay. Keywords: Facilities, Room Rates, Stay Decisions